Analisis Faktor-faktor yang Memengaruhi Struktur Modal pada Perusahaan Sektor Pertanian yang Terdaftar di Bursa Efek Indonesia - Irena Anggita; Rindah F Suryawati (IPB University, 2018)
This study aims to analyze the effect of profitability, firm size, growth, liquidity, and asset structure on capital structure of companies listed in the Agricultural Sector in Indonesia Stock Exchange for the period of 2012 to 2016. The sample in this study totals 14 companies, obtained through purposive sampling technique. This research used fixed effect model that was processed in Eviews program. This study found that the variable of growth, liquidity, asset structure are known to have no effect on the capital structure of the company. Profitability and firm size are known to affect the capital structure where profitability affects negatively and firm size affects possitively.